A laboratory microcosm for simultaneous gas and nutrient flux measurements in sediments - Liikanen, A.; Tanskanen, H.; Murtoniemi, T.; Martikainen, P. J. (Boreal Environment Research Publishing Board, 2024)
We developed a laboratory microcosm to study simultaneously the dynamics of gases and nutrients in sediments. With the microcosm, intact sediment cores were incubated under continuous water flow. The incubation system was constructed so that diffusion and ebullition of gases could be measured separately. Here we show results from an experiment conducted with littoral, shallow and deep profundal sediments of Lake Kevätön using oxic and anoxic water flow. The fluxes of important greenhouse gases (methane, carbon dioxide, and nitrous oxide) and nutrients (phosphorus, ammonium, nitrite and nitrate) were determined. Deep profundal sediments released carbon gases, methane and carbon dioxide, and nutrients, ammonium and phosphorus, especially in anoxic conditions. Also the littoral sediment was important source of methane. Nitrous oxide, nitrite and nitrate were produced in the shallow profundal sediments with the oxic flow. Our microcosm was a promising tool to differentiate gas and nutrient dynamics between sediments under controlled conditions.